Effect of Lutein and Zeaxanthin on Macular Pigment and Visual Function in Patients with Early Age-related Macular Degeneration - Ma, Le; Yan, Shao-Fang; Huang, Yang-Mu; Lu, Xin-Rong; Qian, Fang; Pang, Hong-Lei; Xu, Xian-Rong; Zou, Zhi-Yong; Dong, Peng-Cheng; Xiao, Xin; Wang, Xun; Sun, Ting-Ting; et al. (Ophthalmology (Rochester, Minn.), 2012)
To determine whether supplementation with lutein and zeaxanthin improves macular pigment and visual function in patients with early age-related macular degeneration (AMD). Randomized, double-masked, placebo-controlled trial. Participants with probable AMD who were 50 to 79 years of age were screened for study eligibility from the local communities. One hundred eight subjects with early AMD were recruited. Early AMD patients were assigned randomly to receive 10 mg/day lutein (n = 27), 20 mg/day lutein (n = 27), 10 mg/day lutein plus 10 mg/day zeaxanthin (n = 27); or placebo (n = 27) for 48 weeks. Macular pigment optical density (MPOD) and visual function variables were assessed at baseline, 24 weeks, and 48 weeks. The primary outcome was MPOD. Secondary outcomes were visual function variables including best-corrected visual acuity (BCVA), contrast sensitivity (CS), photorecovery time, and Amsler grid testing results. Macular pigment optical density increased significantly by a mean±standard error of 0.076±0.022 density unit in the 20-mg lutein group and 0.058±0.027 density unit in the lutein and zeaxanthin group during 48 weeks. There was a significant dose-response effect for lutein supplementation, and the changes in MPOD from baseline to 48 weeks were correlated negatively with baseline MPOD in all active treatment groups (r = −0.56; P<0.001). At 48 weeks, a trend toward improvement was seen in BCVA, and there was a significant between-group difference in CS at 3 and 6 cycles/degree between the 20-mg lutein group and the placebo group. The increase in MPOD related positively to the reduction in the logarithm of the minimum angle of resolution BCVA (r = −0.31; P<0.01) and the increases in CS at 4 spatial frequencies (r ranging from 0.26 to 0.38; all P<0.05). Among patients with early AMD, supplementation with lutein and zeaxanthin improved macular pigment, which played a causative role in boosting visual function and might prevent the progression of AMD. Future studies are required to evaluate the effect of these carotenoids on the incidence of late AMD. The author(s) have no proprietary or commercial interest in any materials discussed in this article.